Comparative Analysis of Taxation Techniques and Models used in Digital Economy - Bruce, Mark Rowland; Adekoya, Adebayo Felix; Boateng, Samuel; Appiahene, Peter (International Journal of Economics and Financial Issues, 2022)
In terms of a digital tax, there are certain interesting characteristics of the digital economy and its business structures. Some of these characteristics include mobility, data dependency, network effects, and buildup of multi-faceted business versions, a propensity toward dominance or monopoly, and unpredictability. Our study offers a digital economy model that explicitly accounts for a number of these aspects. The economic structures of platforms are bidirectional, they rely significantly on data collection, and they dominate the market. This model is then used to examine the effect of different taxes suggested to target implicitly dominating digital platforms. The aim of this paper was to examine various digital taxation models that are currently in use in other countries. The paper ends by proposing some recommendations to overcome some of the challenges and issues raised in this paper.